The progress of Mycobacterium tuberculosis drug targets - Zhang, Xin; Zhao, Ruixia; Qi, Yao; Yan, Xiong; Qi, Gaoxiu; Peng, Qiuju (Frontiers in Medicine, 2024)
Tuberculosis (TB) has been troubling humans for hundreds of years, is a highly infectious disease caused by Mycobacterium tuberculosis (Mtb) infection, Mtb can infect almost all organs of the body and is one of the deadly infectious diseases in the world. At present, the first-line treatment regimen has a long treatment cycle and is prone to multiple drug resistance. Anti-tuberculosis drugs and latent tuberculosis infection (LTBI) resistance are increasing year by year, and new targets and new bioactive compounds are urgently needed to treat this disease. This review focuses on the latest reported anti-TB drug targets and related compounds in recent years, reviews the current TB drug regimen and major defects, outlines the key drug targets developed to date in Mtb, and the current situation of newly discovered anti-TB resistant forms of drugs. To provide a reference for the research and development of new anti-TB drugs and bring new treatment strategies for TB patients.